Long-term outcomes of medical therapy versus successful recanalisation for coronary chronic total occlusions in patients with and without type 2 diabetes mellitus - Guo, Lei (Cardiovasc Diabetol, 2020)
BACKGROUND: In this study, we compared the outcomes of medical therapy (MT) with successful percutaneous coronary intervention (PCI) in chronic total occlusions (CTO) patients with and without type 2 diabetes mellitus. METHODS: A total of 2015 patients with CTOs were stratified. Diabetic patients (n = 755, 37.5%) and non-diabetic patients (n = 1260, 62.5%) were subjected to medical therapy or successful CTO-PCI. We performed a propensity score matching (PSM) to balance the baseline characteristics. A comparison of the major adverse cardiac events (MACE) was done to evaluate long-term outcomes. RESULTS: The median follow-up duration was 2.6 years. Through multivariate analysis, the incidence of MACE was significantly higher among diabetic patients compared to the non-diabetic patients (adjusted hazard ratio [HR] 1.32, 95% confidence interval [CI] 1.09–1.61, p = 0.005). Among the diabetic group, the rate of MACE (adjusted HR 0.61, 95% CI 0.42–0.87, p = 0.006) was significantly lower in the successful CTO-PCI group than in the MT group. Besides, in the non-diabetic group, the prevalence of MACE (adjusted HR 0.85, 95% CI 0.64–1.15, p = 0.294) and cardiac death (adjusted HR 0.94, 95% CI 0.51–1.70, p = 0.825) were comparable between the two groups. Similar results as with the early detection were obtained in propensity-matched diabetic and non-diabetic patients. Notably, there was a significant interaction between diabetic or non-diabetic with the therapeutic strategy on MACE (p for interaction = 0.036). CONCLUSIONS: For treatment of CTO, successful CTO-PCI highly reduces the risk of MACE in diabetic patients when compared with medical therapy. However, this does not apply to non-diabetic patients.